Digital Patriarchy and the Framing of Religious Authority: Narratives of Muslim Women on Instagram - Maf’ula, Nur Rahmah Hanim; Zamzami, Mukhammad; Aljahsh, Muhammad Ahmad Ibrahim (Religió Jurnal Studi Agama-agama, 2025)
The study investigates the operation of digital patriarchy through the framing of religious narratives on the Indonesian Instagram account of @ukhtiakhiantiselfie. Employing a descriptive-interpretive approach grounded in Robert N. Entman’s framing theory, the article analyzes how visual content and hadith-based texts construct Muslim women’s bodies as subjects of moral regulation. The findings reveal that women are consistently framed as inherent “moral risks”, legitimizing control through selective, literalist interpretations of sacred texts. However, by engaging with Nur Rofiah’s Islamic feminist hermeneutics and Heidi Campbell’s theory of digital religious authority, the study demonstrates that these digital spaces also serve as arenas for negotiating religious meaning. Ultimately, this research highlights the political and epistemological tensions between the reinforcement of patriarchal norms and the potential for the feminist reconstruction of religious authority in contemporary digital Islam.